(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Alloys based on iron doped by different additions were investigated. Binary alloys containing chromium, molybdenum were investigated at the first stage. It was shown that results of doping by 0.8% molybdenum and tungsten are similar to those for the sample doped by 9%chromium. Ternary alloys containing chromium and less amounts of molybdenum, tungsten and vanadium were investigated as well. Similarity to properties of the alloy containing 0.8% molybdenum was observed for these alloys